“Enhancing Students’ Creative and Analytical Thinking Skills Through Extracurricular Activities in Schools” - Djabbarova Nargiza Bakitovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the role of extracurricular activities in schools for developing students’ creative and analytical thinking skills. The study highlights how interactive teaching methods, project-based learning, and digital resources can foster students’ critical thinking, problem-solving abilities, and innovative mindset. Emphasis is placed on the pedagogical benefits of integrating such approaches into extracurricular programs to increase student engagement, motivation, and independent learning.